Lamellar body count: Marker for foetal lung maturation promoted by intra-amniotic infection and/or inflammation. (June 2022) - Kim, Hyeon Ji; Choi, Hyun Ji; Lee, Kyong-No; Cho, Iseop; Park, Jee Yoon; Oh, Kyung Joon
Highlights: The risk of respiratory distress syndrome is reduced in preterm neonates exposed to intra-amniotic infection and/or inflammation. Lamellar bodies in amniotic fluid are indicative of lung maturation. It is hypothesised that intra-amniotic infection/inflammation could result in elevated lamellar body count (LBC) in the amniotic fluid. The elevation of LBC was independently associated with the presence of intra-amniotic infection/inflammation in women with early threatened preterm birth. Abstract: Objective: There is evidence indicating that the risk of respiratory distress syndrome is reduced in preterm neonates exposed to intra-amniotic infection and/or inflammation. We hypothesised that foetal lung maturation promoted by intra-amniotic infection and/or inflammation results in elevated lamellar body count (LBC) in amniotic fluid (AF). This study aimed to determine the relationship between LBC in AF and intra-amniotic infection and/or inflammation in patients with threatened preterm birth. Study design: This was a retrospective cohort study of patients with threatened preterm birth. A total of 104 consecutive pregnant women underwent amniocentesis in the early preterm period [gestational age < 34 weeks] to evaluate intra-amniotic infection and/or inflammation and foetal lung maturity. Intra-amniotic infection was confirmed by positive AF culture results for aerobic/anaerobic bacteria, fungi, and genital mycoplasma. Intra-amniotic inflammation was defined as a positive AF matrix metalloproteinase-8 rapid test. Outcomes of the study population were compared according to LBC in AF using a cut-off of 15, 000/mm 3 . Results: The rates of elevated LBC and intra-amniotic infection and/or inflammation were 23% (24/104) and 52% (54/104), respectively. The median LBC was significantly higher in patients with intra-amniotic infection and/or inflammation than in those without [median LBC, 9, 000/mm 3 (interquartile range, IQR: 3, 000–39, 000) vs. 3, 000/mm 3 (IQR: 2, 750–5, 000), p < 0.001]. Intra-amniotic infection and/or inflammation was observed in 96% (23/24) of patients with elevated LBC and 39% (31/80) of patients without elevated LBC (p < 0.001). On multivariable analysis, the presence of intra-amniotic infection and/or inflammation was significantly associated with elevated LBC with an odds ratio (OR) of 66.0 [95% confidence interval (CI) 6.6–664.4, p < 0.001], even after accounting for gestational age at amniocentesis being a significantly related factor for predicting elevated LBC with an OR of 1.5 (95% CI 1.1–2.0, p = 0.004). Conclusion: LBC elevation was independently associated with the presence of intra-amniotic infection and/or inflammation in women with early threatened preterm birth (gestational age < 34 weeks). This finding may support the view that an intra-amniotic inflammatory response promotes foetal lung maturation that can be detected by elevated LBC in AF.